2018
DOI: 10.1111/gcb.14384
|View full text |Cite
|
Sign up to set email alerts
|

Storm impacts on alpine lakes: Antecedent weather conditions matter more than the event intensity

Abstract: Extreme weather events may be just as important as gradual trends for the long-term trajectories of ecosystems. For alpine lakes, which are exposed to both exacerbated atmospheric warming and intense episodic weather events, future conditions might not be appropriately forecast by only climate change trends, i.e. warming, if extreme events have the potential to deflect their thermal and metabolic states from their seasonal ranges. We used high-frequency monitoring data over three open-water seasons with a one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 61 publications
(106 reference statements)
1
56
0
1
Order By: Relevance
“…Similarly, for lakes on a long‐term changing environmental trajectory such as increasing eutrophication, a storm may appear to have a lasting impact but merely accelerated a “natural” progression (Bachmann et al, 1999; Clugston, 1963; Havens et al, 2001; James et al, 2008). Many of the studies in our systematic review observed that the trajectory of the communities and the duration of storm effects was highly variable and could be related to antecedent conditions (Perga et al, 2018) or a consequence of sampling frequency (James et al, 2008; Padisák, Tóth, & Rajczy, 1990).…”
Section: Research Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, for lakes on a long‐term changing environmental trajectory such as increasing eutrophication, a storm may appear to have a lasting impact but merely accelerated a “natural” progression (Bachmann et al, 1999; Clugston, 1963; Havens et al, 2001; James et al, 2008). Many of the studies in our systematic review observed that the trajectory of the communities and the duration of storm effects was highly variable and could be related to antecedent conditions (Perga et al, 2018) or a consequence of sampling frequency (James et al, 2008; Padisák, Tóth, & Rajczy, 1990).…”
Section: Research Directionsmentioning
confidence: 99%
“…The same storm will impact different lakes in different ways (Klug et al, 2012; Kuha et al, 2016), and the same lake will respond to different storms in different ways depending on antecedent conditions (see below) and the incidence of compound climatic events (Leonard et al, 2014; Perga et al, 2018). Consequently, “strength” of a storm is necessary but not sufficient to understand the degree to which storms impact light, nutrients, and temperature and thus phytoplankton community dynamics.…”
Section: Lake and Watershed Attributes As Mediators Of Storm Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions leading up to a storm event may also be significant in predicting the impact. Perga et al, for example, showed that antecedent weather conditions were important in determining storm impact on lake turbidity in alpine lakes [17].Untangling this web of drivers of storm impacts on lakes can only be achieved by investigating a large number of storms of varying strength and duration, occurring at times when internal parameters within the lake, such as thermocline depth, water temperature and water column stability, are also changing. It requires a long time series of high frequency data on water column temperature profiles, data archives that are scarce in Europe and globally [18].…”
mentioning
confidence: 99%
“…It requires a long time series of high frequency data on water column temperature profiles, data archives that are scarce in Europe and globally [18]. Single storm events have been investigated before [6,13,15,16,19], some studies have investigated several storms occurring over months or few years [5,17,20,21], but to our knowledge no studies to date have looked at large numbers of storm events over many years in one lake.In the present study, we investigated the effect of storms on physical conditions in Lough Feeagh, Co. Mayo, Ireland (Figure 1), during fully mixed conditions in winter and in the stratified period in summer. We quantified the changes in a range of lake physical parameters including energy flow (heat fluxes), temperature change, water column stability and thermocline depth.…”
mentioning
confidence: 99%